SISTEM PENDUKUNG KEPUTUSAN KELAYAKAN PEMBERIAN KREDIT MODAL USAHA MENERAPKAN METODE FUZY TSUKAMOTO (STUDI KASUS : PT. BPR BINA BARUMUN) - Tanjung, Nur Sakinah; Mesran, Mesran; Tampubolon, Kennedi; Suginam, Suginam; Sianturi, Maringan (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Credit is increasingly growing and is increasingly needed by the wider community, people who do not have the capital to establish a business generally prefer to do credit or borrow money to trusted parties such as banks to support the business to be established. This is an advantage for the bank. Increasing credit activities in banks, it is necessary to assess credit as a material consideration for prospective customers before the bank gives a decision to accept or reject a prospective customer request. Therefore it is necessary to build a method that can help and facilitate the bank in giving decisions quickly and accurately. The basis for making decisions is based on the criteria to determine who is prioritized to receive a loan, to assist in determining in determining someone who is eligible to receive a loan, so a decision support system is needed is to use Fuzzy logic and apply the Tsukamoto method. Decision Support Credit Provisioning System is made for the purpose of assisting and facilitating the bank as the decision maker to provide alternatives in the event of a credit application being accepted or not.Keywords: Creditworthiness, Decision Support System, Fuzzy Tsukamoto